Histochemical Studies on Digenetic Trematode Parasite, Orientocreadium striatusae n.sp. from Channa striatus (Bloch, 1793) - C.J. Hiware*, P.R. Pardeshi and (Recent Research in Science and Technology, 2010)
Phosphatases have been localized by histochemical techniques in various organ of piscian digenetic trematode parasite, Orientocreadium striatusae n.sp. Alkaline and acid phosphatases were present in almost all structure viz., suckers, testes, ovary, uterus, seminal receptacles, egg shell and vitellaria.